Perancangan Mold Base Dengan Sistem Two Plate Mold Untuk Produk Spesimen Uji Tarik - Mario Sariski Dwi Ellianto; Pongky Lubas Wahyudi (Motor Bakar : Jurnal Teknik Mesin, 2023)
A mold is a tool for printing plastic products. The way it works is by installing the mold on a plastic injection machine, and then the machine does the injection process to put molten plastic material into the mold. In the mold, there is a cavity that matches the shape of the product to be made. Before a mold can be used, it must be designed and manufactured. ATK Polytechnic of Yogyakarta has one injection molding machine with several molds available. The available molds do not yet have a design based on various information, analysis, and calculations, so this research will make a mold design that is expected to be a guideline for making plastic injection molds and is expected to be able to analyze the needs for cavities, gates, ejector systems, cooling system. In this study, the design and calculation of mold construction, including the cavity, parting line, gate, ejector, cavity plate, core plate, runner, and cooling, were discussed. The purpose of this study is to determine how to design a basic mold construction with a two-mold plate system, with the resulting product being a tensile test specimen. The result of this tensile test specimen mold design is a mold base design drawing with a mold size of 350mm x 500mm x 255mm, the number of cavities being 4 cavities per mold, and the volume of the tensile test specimen mold being 33.0122 cm3.